Upaya Pengelolaan Asma Bronkial pada Pasien Perempuan Usia 20 Tahun dengan Pendekatan Pelayanan Kedokteran Keluarga di Puskesmas Kuta Makmur Kabupaten Aceh Utara - Raudah Novita Putri; Noviana Zara (Inovasi Kesehatan Global, 2025)
A 20-year-old female patient came with a complaint of cough that had been experienced for ± 1 week, the cough was complained of as difficulty in expelling phlegm. The cough worsened at night and early morning so that it disrupted the patient's sleep quality. The cough would subside when the conditions started to warm up, and when drinking water. Shortness of breath often appears together with the cough. Complaints of shortness of breath and cough often appear during the rainy season, cold air, exposure to dust and smoke. Shortness of breath will subside if the patient uses an inhaler. The patient also complained of a fever that had been felt since 1 day ago. The fever felt by the patient remained high without any decrease in temperature. On physical examination, BP was 110/70 mmHg, RR 18 x / minute, HR 89 x / minute, BMI 19.6 kg / m2., Respiratory system wheezing in both lungs and X-ray results showed bronchitis. Primary data were obtained through anamnesis and physical examination by conducting home visits, filling out family folders, and filling out patient files. The assessment is based on the initial holistic diagnosis, process, and end of the visit quantitatively and qualitatively. The interventions carried out are promotive, preventive, curative, rehabilitative and psychosocial efforts.